Pyrosequencing and de novo assembly of Antarctic krill (Euphausia superba) transcriptome to study the adaptability of krill to climate‐induced environmental changes. (9th April 2015) - Meyer, B.; Martini, P.; Biscontin, A.; De Pittà, C.; Romualdi, C.; Teschke, M.; Frickenhaus, S.; Harms, L.; Freier, U.; Jarman, S.; Kawaguchi, S.
Abstract The Antarctic krill, Euphausia superba, has a key position in the Southern Ocean food web by serving as direct link between primary producers and apex predators. The south‐west Atlantic sector of the Southern Ocean, where the majority of the krill population is located, is experiencing one of the most profound environmental changes worldwide. Up to now, we have only cursory information about krill's genomic plasticity to cope with the ongoing environmental changes induced by anthropogenic CO2 emission. The genome of krill is not yet available due to its large size (about 48 Gbp). Here, we present two cDNA normalized libraries from whole krill and krill heads sampled in different seasons that were combined with two data sets of krill transcriptome projects, already published, to produce the first knowledgebase krill 'master' transcriptome. The new library produced 25% more E. superba transcripts and now includes nearly all the enzymes involved in the primary oxidative metabolism (Glycolysis, Krebs cycle and oxidative phosphorylation) as well as all genes involved in glycogenesis, glycogen breakdown, gluconeogenesis, fatty acid synthesis and fatty acids β‐oxidation. With these features, the 'master' transcriptome provides the most complete picture of metabolic pathways in Antarctic krill and will provide a major resource for future physiological and molecular studies. This will be particularly valuable for characterizing the molecular networks that respond to stressors caused by the anthropogenic CO2 emissions and krill's capacity to cope with the ongoing environmental changes in the Atlantic sector of the Southern Ocean.